Sustainable operations and computers (KeAi Communications Co. Ltd. Publishing services by Elsevier B.V. on behalf of KeAi Communications Co. Ltd, 2020)
"Sustainable Operations and Computers is an interdisciplinary journal focus on topics that manages the balances, tradeoffs, and synergies associated with the integration of economics, environment and social perspectives into traditional decision-making processes. This means that a wide variety of businesses and operations management problems under the sustainability and climate change domain are in general covered by this journal. Concerns such as energy and water usage efficiency in production, recycling and remanufacturing planning, reducing carbon emissions in operations, managing scarcity of raw materials, waste management, managing sustainable supply chains, disaster management, and emerging problems such as migration crisis are emblematic of the new complex issues facing production and operations managers globally"--
Keywords: Decision making : Data processing : Periodicals; Decision making : Data processing; Toma de decisiones; Proceso de datos